The Political Impact of Media Bias on Electoral Process - Shabeer Ullah; Arshad Ali; Atif Ur Rehman (Journal of Peace, Development and Communication, 2020)
In a democratic society, political beliefs, attitudes, behaviors, and political choices of the electorates affect elections policy outcomes. Mass media play a vital role in shaping opinions, manipulating political behaviors, and influencing the electoral process. The study maintains that electorates defend on the mass media for getting information about political parties and candidates during the election campaigns. The study investigates the political impact and influence of media bias over political opinions and the electoral processes through a survey to determine the relationship between media bias and its influence on election outcomes and political decision-making. The researcher distributes the questionnaire to 300 students enrolled in public sector universities to generalize the responses and gauge the political impact of media bias. The study provides evidence about bias in the political contents of media and the extent to which the political content of media persuades and mobilizes voters. The study reveals that mass media bias influences political beliefs and opinions of the public through the selective presentation of facts in a subjective manner. The consequences help comprehend the special effects news media bias had on political behaviors and the election result. The study confirmed that media bias shapes political opinions, persuade voters, and exercise strong influence over the electoral process and election outcomes.